Recovery Time from Severe Acute Malnutrition and Development of Complementary Food Supplement For Affected Ethiopian Children - Desalegn Gebrezgi; Degnet Teferi; Prasad PCJ Reddy (International Journal of Nutrition, 2019)
Background: Severe acute mal nutrition (SAM) among children still remains the major problem in Ethiopia. The shortening of the SAM recovery time by applying appropriate dietary means during treatment and also after recovery, can save huge sums of public health spending. Objectives: Determining the recovery time of SAM affected children and developing complementary food supplement (CFS). Methods: Hospital based retrospective cohort study was carried out on 401 SAM affected children. A structured and pre tested data abstraction form was used for data collection. The data were entered into Epi info and exported to SPSS for analysis. All of the nutritional properties of the developed product in three different ratios of the flours of maize, soybean and powder of moringaolifera leaves were assessed and compared to the control (100% maize). Results: The median recovery time was 16 days. There was a significant increase in protein, mineral and beta carotene content with increasing level of Moringaolifera leaf powder in the CFS. Conclusion: To increase the rate of recovery from sever acute malnutrition and also to prevent relapsing, moringa incorporated cheaper complementary fod supplements could be recommended for SAM affected children.
Keywords: microbiota